Agraphis nutans in Treatment of Chronic Tonsillitis: Randomised, Pragmatic, Equivalence Trial - Chakraborty, Sunanda; Uchat, Usha Ghelani; Ghosh, Priyanka; Singh, Navin Kumar; Koley, Munmun; Saha, Subhranil (Homœopathic Links, 2022)
Background Agraphis nutans (AN) is a potential homeopathic medicine in the treatment of chronic tonsillitis, but has remained under-researched. This trial attempts to compare the effects of AN with individualised homeopathic medicines (IHMs) in the treatment of chronic tonsillitis in adults.Methods An open, randomised, pragmatic, equivalence trial was conducted to compare the effects of AN with IHMs. Sixty adults suffering from chronic tonsillitis were randomised to receive either AN (n = 30) or IHMs (n = 30). Three visual analogue scales (VASs) in the sore throat pain model (STPM) – sore throat pain intensity scale (STPIS), difficulty swallowing scale (DSS) and swollen throat scale (swoTS)—were used as the primary outcome while tonsil and adenoid health status instrument (TAHSI) and Glasgow benefit inventory (GBI) as the secondary outcomes; and they were measured after 6 and 12 weeks. Intention-to-treat sample was analysed to detect non-inferiority of AN against IHMs and group differences using two-ways (split-half) repeated measure analysis of variance and unpaired t-tests.Results Reductions in all three STPM-VASs, TAHSI and GBI total and subscale scores were significant in the IHMs group (all p < 0.001, except TAHSI halitosis and nocturnal breathing subscale scores), but not in the AN group. Still, except GBI, non-inferiority was exhibited by AN against IHMs in rest of the outcomes after 6 and 12 weeks (all p < 0.001). Hepar sulphuris calcareum (n = 11; 36.7%) and Mercurius solubilis (n = 3; 10%) were the most frequently prescribed remedies in the IHMs group.Conclusion AN performed non-inferior to IHMs in treatment of chronic tonsillitis in adults; however, it may result from suppression of symptoms. Rigorous and larger trials are warranted.Trial Registration: CTRI/2018/10/016233; UTN: U1111–1221–8221.
Keywords: Agraphis nutans; chronic tonsillitis; homeopathy; quality of life; randomised controlled trial